Possessive Constructions in Egyptian and Coptic. Distribution, Definiteness, and the Construct State Phenomenon - Egedi, Barbara (Zeitschrift für ägyptische Sprache und Altertumskunde, 2010)
In this paper, the distribution of Coptic possessive constructions is defined in terms of syntactic constraints: the construction involving the linking element n - requires the obligatory (and simple) definiteness of the possessed noun as well as the strict adjacency of regens and rectum . In relation to a comparison made between this Coptic possessive pattern and the so-called construct state phenomenon, a historical overview of the Egyptian language is given to explore the possible reconstruction of a true construct state formation in the earlier language stages.